Disconnected : youth, new media, and the ethics gap - James, Carrie (Cambridge, Massachusetts : The MIT Press, 2014)
"Drawing on extensive interviews with young people between the ages of 10 and 25, James describes the nature of their thinking about privacy, property, and participation online. She identifies three ways that young people approach online activities. A teen might practice self-focused thinking, concerned mostly about consequences for herself; moral thinking, concerned about the consequences for people he knows; or ethical thinking, concerned about unknown individuals and larger communities. James finds, among other things, that youth are often blind to moral or ethical concerns about privacy; that attitudes toward property range from "what's theirs is theirs" to "free for all"; that hostile speech can be met with a belief that online content is "just a joke"; and that adults who are consulted about such dilemmas often emphasize personal safety issues over online ethics and citizenship. Considering ways to address the digital ethics gap, James offers a vision of conscientious connectivity, which involves ethical thinking skills but, perhaps more important, is marked by sensitivity to the dilemmas posed by online life, a motivation to wrestle with them, and a sense of moral agency that supports socially positive online actions."--Publisher's description.
Morality, ethics, and digital life -- Privacy -- Property -- Participation -- Correcting the blind spots, reconnecting the disconnects.
Includes bibliographical references (pages 131-159) and index.
Keywords: Internet and youth; Internet -- Moral and ethical aspects; Parental influences; Internet and youth; Internet -- Moral and ethical aspects; Parental influences